Smart Battery Storage Integration in An IoT-Based Solar-Powered Waste Management System - Olatunbosun A Ajibola; Omolola A Ogbolumani (Journal of Digital Food, Energy & Water Systems)
With over 33% of the world's 2.01 billion tons of annual solid waste managed poorly and projections of 3.40 billion tons by 2050, the global waste crisis is escalating. As daily per capita waste ranges from 0.11 to 4.54 kilograms, low-income countries face a tripling of waste production by 2050. Traditional waste management systems are inefficient and contribute to environmental pollution and operational costs. To address these challenges, integrating smart battery storage with IoT-powered solar waste management offers a sustainable alternative. By harnessing solar energy and storing it in smart batteries, these systems ensure the continuous operation of IoT devices, sensors, and waste collection vehicles, reducing reliance on grid power and carbon emissions. A prototype system, designed, developed, and simulated using Proteus circuit simulation, incorporates IoT sensors, solar panels, and smart battery storage to optimise energy use and improve waste collection efficiency. The research findings contribute to advancing sustainable waste management practices and inform the development of similar IoT-based systems for various urban applications.